Observational Study on Impact of Pathyapathya in Prevention of Sthoulya (Obesity) (AYUSHDHARA, 2023)
Weight gain is a natural physiological process but excess of fat leading to the disease Sthoulya (obesity) may “lengthen the waist line” but “shortens the life-line” of the individual by imposing an extra burden on all the systems. Aim: To study the impact of Pathyapathya in prevention of Sthoulya (obesity) among college students of VYDSAM. Materials and Methods: A randomized open observational Study was conducted at the hospital of VYDSAM, Khurja, using a special diet (menu) planner and exercise planner adopted for weight reduction. Total 450 students were screened through BMI, 33 Sthoulya (obesity) cases were selected for trial and 30 cases completed the trial. Relief in the subjective symptoms was assessed in percentage. Then, the statistical significance of result was assessed using Wilcoxon matched‑pairs signed‑ranks test. Results: Defining to the benefits assessed, Pathyapathya proved to be quite effective in prevention of Sthoulya (obesity) as statistical evaluation shows extremely/very significant effect on various clinical features. Weight loss occurs in Pathyapathya because of decreased caloric intake and increases people's total energy expenditure by Physical activity. The burning of calories through physical activity, combined with reducing the number of calories in diet, creates a “calorie deficit” that results in weight loss. Conclusion: The overall effect of therapy on clinical assessment leading to Maximum, Moderate, Mild and Unsatisfactory was 6 (20%), 15 (50%), 7 (23.33%) and 2 (6.67%) respectively. The percentage of improvement in subjective, objective parameters and lipid profile highlights the poor prognosis of Sthoulya (obesity) managed alone with Pathyapathya. So for better result, Shamana medications and Shodhana procedures may add along with Pathyapathya.